2002
DOI: 10.1007/s00221-001-0929-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary sensory neurons and satellite cells after peripheral axotomy in the adult rat

Abstract: The timecourse of cell death in adult dorsal root ganglia after peripheral axotomy has not been fully characterised. It is not clear whether neuronal death begins within 1 week of axotomy or continues beyond 2 months after axotomy. Similarly, neither the timecourse of satellite cell death in the adult, nor the effect of nerve repair has been described. L4 and L5 dorsal root ganglia were harvested at 1-14 days, 1-6 months after sciatic nerve division in the adult rat, in accordance with the Animals (Scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(58 citation statements)
references
References 30 publications
2
55
0
1
Order By: Relevance
“…Subsequently, Wallerian degeneration may arise distal to the lesion [14,17]. It has been shown that sciatic nerve crush leads to histological changes in the DRG cells number [33]. Loss of the neurons occurs and the nerve cells become less after peripheral nerve injury in the DRG [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Wallerian degeneration may arise distal to the lesion [14,17]. It has been shown that sciatic nerve crush leads to histological changes in the DRG cells number [33]. Loss of the neurons occurs and the nerve cells become less after peripheral nerve injury in the DRG [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes show morphological similarities with the process of apoptosis, which occurs in adult DRG neurons within one week of axotomy, peaks in 2 months, and continues as late as 6 months 59,60. Comparable to our findings in DRG neurons, apoptosis in cultured sympathetic neurons diminishes the extent of ER 61.…”
Section: Discussionmentioning
confidence: 85%
“…Axotomy of sensory nerves at adulthood often leads to the death of their ganglion cells (Aldskogius and Arvidsson, 1978; Aldskogius et al, 1985; Arvidsson and Grant, 1979; Groves et al, 1997; McKay Hart et al, 2002; Morest et al, 1998; Persson et al, 1991; Spoendlin, 1984; Westrum et al, 1976; Zuniga, 1999). A similar loss of geniculate ganglion cells following CTX may account, in part, for the reduced labeled terminal field volume that we show here.…”
Section: Resultsmentioning
confidence: 99%